Komunikasi Antara Orang Tua dengan Anak dan Pengaruhnya terhadap Perilaku Anak - Rawit Sartika; Panji Sutrariadi (Departement of Mathematics Education, 2024)
Communication between parents and children can be seen as an effort to find out, monitor and direct the development of children, because no matter how mature children are, they still really need someone who is considered more mature so that they can protect them properly. By creating effective and efficient communication between parents-children or vice versa, it is hoped that children can develop well physically and psychologically. This study aims to determine how much influence parent-child communication has on children's behavior. This research method that the author uses is Descriptive Analysis method. While the approach used in this study is correlational, namely to seek the influence between the two variables. The sampling technique in this study used random sampling. The results showed that there was a positive correlation between parental communication and the behavior of students in class VIII A and C at SMPN 13 Bogor. This can be seen from the magnitude of the calculation results obtained with a value of rxy = 0.59 which lies in the category between 0.40-0.70 which means the correlation is sufficient. And this is shown at the 1% significance level rxy or ro is greater than the r table (0.59>0.325), so at this level the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, this means that at the 1% and 5% significance levels there is a positive correlation between the X and Y variables.